Security needs and the performance of the defense industry - Andreas Blume; Asher Tishler (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
Today, leading defense firms are concentrated into just two distinct blocs . those based in the US and those in Western Europe. All US defense firms and most European ones are private. Market structure may thus play an important role in determining procurement levels as well as defense policies in the US and Europe. This paper focuses on the interactions between defense needs and market structure. It presents a model in which two producer blocs (representing the US and Europe) produce an identical homogeneous defense good. The .rest of the world. purchases the defense good from the two producer countries. The security level of each of the two producing countries depends on its purchase of the defense good relative to the amount of defense good purchased by the rest of the world. Each country measures its security level against a target that it sets for itself. – – Heute sind die führenden Rüstungsunternehmen in zwei unterschiedlichen Regionen konzentriert: in den USA und in Westeuropa. Alle US-Unternehmen und die meisten europäischen Unternehmen sind in Privatbesitz. Insofern kann die Marktstruktur als wichtige Einflußgröße des Beschaffungsniveaus und der Verteidigungspolitik in den USA und Europa angesehen werden. Der Beitrag konzentriert sich auf die Interaktion zwischen Verteidigungsbedürfnissen und Marktstruktur. Es wird ein Modell vorgestellt, in dem zwei .Produzentenblöcke. (die USA und Europa) ein identisches, homogenes Rüstungsgut produzieren. Der .Rest. der Welt kauft die Rüstungsgüter von den beiden Herstellerländern. Das Sicherheitsniveau jedes der beiden Länder hängt von seiner Beschaffung der Rüstungsgüter im Vergleich zum Beschaffungsvolumen an Rüstungsgüter durch den Rest der Welt ab. Jedes Land bestimmt sein Sicherheitsniveau im Vergleich zu einem selbstgesteckten Ziel.
Keywords: 330; defense industry; technology; security level; market structure